2015
DOI: 10.3109/08958378.2015.1013227
|View full text |Cite
|
Sign up to set email alerts
|

Study of cardiovascular disease biomarkers among tobacco consumers, part 2: biomarkers of biological effect

Abstract: An age-stratified, cross-sectional study was conducted in the US among healthy adult male cigarette smokers, moist snuff consumers, and non-tobacco consumers to evaluate cardiovascular biomarkers of biological effect (BoBE). Physiological assessments included flow-mediated dilation, ankle-brachial index, carotid intima-media thickness and expired carbon monoxide. Approximately one-half of the measured serum BoBE showed statistically significant differences; IL-12(p70), sICAM-1 and IL-8 were the BoBE that best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 68 publications
(115 reference statements)
2
16
0
Order By: Relevance
“…On the other hand, a more recent, albeit smaller study, found no significant difference (p ¼ 0.09) (Bazzano et al 2003). In another study, there was no reduction in FBG levels in subjects who refrained from smoking for 1 year (King et al 2017) One study found no significant difference between smokers who continued to smoke conventional cigarettes compared to those who switched to an RRP (p ¼ 0.88) (Nordskog et al 2015). It is important to note that many studies have shown that the functionality of FBG as an acute phase protein in response to inflammatory conditions is better reflected in changes in CRP than in corresponding changes of FBG levels (Al Rifai et al 2017).…”
Section: Fibrinogen (Fbg)mentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, a more recent, albeit smaller study, found no significant difference (p ¼ 0.09) (Bazzano et al 2003). In another study, there was no reduction in FBG levels in subjects who refrained from smoking for 1 year (King et al 2017) One study found no significant difference between smokers who continued to smoke conventional cigarettes compared to those who switched to an RRP (p ¼ 0.88) (Nordskog et al 2015). It is important to note that many studies have shown that the functionality of FBG as an acute phase protein in response to inflammatory conditions is better reflected in changes in CRP than in corresponding changes of FBG levels (Al Rifai et al 2017).…”
Section: Fibrinogen (Fbg)mentioning
confidence: 95%
“…ICAM-1 expression can be induced by proinflammatory cytokines, which are also thought to signal its shedding from the membrane so that it can be detected as soluble ICAM-1 (sICAM-1) in serum or plasma. Smokers have significantly higher plasma sICAM-1 levels (145.1 ng/mL) than non-smokers (110.3 ng/mL) (p < 0.0001), which was associated with endothelial dysfunction and clinical CVD (Nordskog et al 2015). Studies have shown that ICAM-1 is overexpressed in the airway epithelium of subjects with COPD (Gross et al 2012) and that release of sICAM-1 by bronchial epithelial cells following smoke exposure is significantly elevated in COPD (Chan et al 2008, Rusznak et al 2000.…”
Section: Soluble Intercellular Adhesion Molecule (Sicam-1)mentioning
confidence: 98%
“…Data set 3: Cross-sectional study of male tobacco consumers and never consumers of tobacco: A single site, cross-sectional study was conducted between September 2008 and February 2009 in the US to evaluate several biomarkers of tobacco exposure and biological effect in exclusive SMK ( n = 60), exclusive moist snuff consumers (MSC, n = 48), and NTC ( n = 60) (ClinicalTrials.gov Identifier: NCT01692353). Details have been reported elsewhere (Campbell et al, 2015 ; Nordskog et al, 2015 ). Briefly, participants were generally healthy males, aged 26–49 years.…”
Section: Methodsmentioning
confidence: 99%
“…Biomarkers of tobacco and tobacco smoke exposure (BoE) were additionally evaluated and are reported here along with a description of the study design and conduct. Comparisons of biological effect biomarkers and physiological assessments are reported elsewhere (Marano et al, 2015 ; Nordskog et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%